The Effect of Labirin Media on the Ability of Children's Problem Solving in Early Childhood Education Barokah Citra in Talang Cempedak Ogan Komering Ilir - Melinda Puspita Sari Jaya; Try Indah (Departement of Mathematics Education, 2023)
This study aims to determine the effect of labyrinth media on children's problem solving abilities in Barokah Citra Early Childhood Education at Talang Cempedak Ogan Komering Ilir. The population is 20 people and the sample of children aged 5-6 years in class B1 is 10 people. The research method used in this research is an experimental method with the One-group Pre-Test and Post-test design. Data collection techniques in research are observation and documentation. Data analysis techniques using the normality test, homogeneity test (F test) and hypothesis testing (t test). The results of this study indicate that based on the calculations obtained, the researcher concludes that the labyrinth media has a significant influence on the ability to solve problems in children, of course this can be seen from the increase in children's scores when giving the pretest and when giving the posttest where the child is able to play the puzzle more well after being given treatment using labyrinth media. The data has been included in the test, namely the hypothesis test T test Fcount <Ftable with a level = 0.05. In this study, the F test was carried out to test the homogeneity of the data and obtained Fcount = 1.14 <Ftable = 3.18 which stated that HO was rejected, Ha was accepted.